"Muslim Minority in the Portuguese Kingdom (1170-1496): identity and writing" - Barros, Maria Filomena Lopes de (2015)
The historical perspective of Muslim minority (as the Jewish one) is subjected to a mediated discourse, based mainly upon documentation produced or controlled by the Christian powers. Even so, it is possible to trace the identity marks of this minority in the written records, mainly in production of Islamic Law or in other documental levels that registered services rendered to the Portuguese king in Islamic territories. A bipartite identity expressed in Portuguese, in an adscription to the King and the realm, in their assumption of the legal statute of mouro forro (free moor), and in Arabic, as garīb, in their relation to the Islamic umma.